Teachers’ view in improving students’ speaking ability through pictures - Muflihatun Muflihatun; Bustami Usman; Nira Erdiana (Universitas Syiah Kuala, 2017)
In curriculum 2013, students are expected to use English in oral communications related to the skill pictures are frequently use teaching. Descriptive is a text that often use in speaking. Unfortunately, student lack of vocabulary, no ideas, and not enough information to describing something in detail; based on the problems, teachers’ try to solve it in classroom activity. One of them is media picture that used by teacher to attract student’s attention and motivations. This study was descriptive qualitative. To find the data the researcher ask teachers’ view’ on the impact of media picture in improving students speaking ability; by using interview and recorded. The researcher found that positive view of teachers’ related to pictures. In addition, pictures are easy to obtain, colorful is better to attract students’ attentions. It was give many contributions in field of education.